The 2024 ESC Guidelines for Chronic Coronary Syndromes: A Paradigm Shift in Risk Stratification and Therapeutic Strategies - Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2025)
The 2024 European Society of Cardiology (ESC) guidelines on chronic coronary syndromes (CCS) introduce significant refinements in diagnosis, risk stratification, and therapeutic strategies, underscoring a shift toward precision medicine and personalized patient care. Moving beyond traditional phenotype classifications, CCS is now recognized as a spectrum, with risk assessment enhanced by coronary artery calcium scoring (CACS) and the risk factor-weighted clinical likelihood (RF-CL) model, improving predictive accuracy for adverse cardiovascular events. Therapeutic updates include optimized dual antiplatelet therapy (DAPT), clopidogrel monotherapy, and expanded use of P2Y12 inhibitors, aiming to balance ischemic protection with bleeding risks. The guidelines further reinforce the cardiovascular benefits of glucagon-like peptide-1 (GLP-1) receptor agonists and sodium–glucose cotransporter 2 (SGLT2) inhibitors beyond diabetes care. A comparison between ESC 2019 and ESC 2024 underscores a more individualized approach to CCS management, incorporating non-invasive imaging such as coronary computed tomography angiography (CCTA), cardiac magnetic resonance imaging (CMR), and positron emission tomography (PET)/single-photon emission computed tomography (SPECT) to refine diagnostic accuracy, while emphasizing the diamond model for medical therapy tailored to coronary pathophysiology and symptom severity. Additionally, the guidelines explore the role of anti-inflammatory therapies, particularly low-dose colchicine, in reducing cardiovascular events, reinforcing a paradigm shift toward integrated, risk-adapted strategies. These advancements signal a holistic transformation in CCS management, combining precision medicine, cutting-edge imaging tools, and emerging pharmacotherapies to enhance clinical decision-making and long-term patient outcomes, while future research should focus on refining antithrombotic regimens, assessing novel lipid-lowering agents, and evaluating anti-inflammatory strategies to ensure sustained improvements in cardiovascular care.